(untitled) (Journal of actual problems of jurisprudence, 2018)
In this article it is told about ancient traditions and customs of tribes, formation of the hansky power, is also considered social importance of laws, traditions in the company of Kazakhs in the course of formation in Kazakhstan of statehood. The analysis of political and social and economic processes of emergence on immense space of Desht-i-Kipchaka of association of Kazakhs, before emergence of the code of laws of «Жеті Жарғы» was carried out. Key words: common law, kazakh society, social state.